A Study on the Flora and Fauna of Jim Corbett National Park: Exploring the Biodiversity and Socio-Economic Dynamics of the Park (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Corbett National Park is well known for its one of kind environments, for example, various sorts of woodlands with wetlands and large meadows which are designated Chaurs in neighborhood language. Park has Sal and Anogeissus blended woods and Tiger as a lead animal varieties. Corbett National Park is situated in Uttarakhand, along the eastern edge of the Ramganga River. The vegetation in these western Himalayan lower regions comprises generally of dry and soggy deciduous woodlands, scour savannah and alluvial fields (Kandpal 2006). CNP is rich in faunal variety, with 50 types of vertebrates, 575 types of birds, and critical tiger and elephant populaces The greater part of the occupants of the 92 towns encompassing the timberland region rely upon 'support zone' backwoods regions for fuel wood, feed, and for touching domesticated animals This woods likewise upholds spill-over populaces of natural life from the national park region. Thusly, human-natural life struggle is high around here because of episodes of untamed life harm to harvests, animals and human existence and the ensuing reprisal by locals. Be that as it may, challenges looked by the visit administrators make it amazingly hard for them to satisfy their job in natural life the travel industry. Further, results from the review directed with the agents of the nearby networks were partitioned into two areas – the primary segment gave a clear investigation of the example of the neighborhood networks, though, the subsequent segment portrayed the disposition of local people towards different parts of untamed life the travel industry.